2013
DOI: 10.1097/ico.0b013e3182662390
|View full text |Cite
|
Sign up to set email alerts
|

Tear Osmolarity and Dry Eye Symptoms in Women Using Oral Contraception and Contact Lenses

Abstract: Purpose To examine the relationship between oral contraceptive pill (OCP) use, contact lens wear, and dry eye signs and symptoms in healthy young females. Methods Fifty-two women using OCPs and forty-five women not using any form of hormonal contraception were enrolled. Medical, menstrual, and contact lens histories were obtained and dry eye symptoms were assessed using the Ocular Surface Disease Index (OSDI) and Symptom Assessment iN Dry Eye (SANDE) questionnaires. Tear osmolarity testing was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 35 publications
(48 reference statements)
1
52
0
1
Order By: Relevance
“…This is in agreement with the results reported by Chen et al, who found that SANDE consistently scored symptoms higher than OSDI in various groups of patients with DED. 17 A difference of 14 points would be, in fact, of clinical significance according to Miller et al 12 However, when algebraic-vectorial normalization was applied to the scores obtained with both questionnaires, we found a difference of less than 2 units. While the magnitude of this difference remained constant in the two different measurements (baseline and follow-up) the signs alternated between both measurements, supporting the idea that the difference is negligible.…”
Section: Discussionmentioning
confidence: 62%
“…This is in agreement with the results reported by Chen et al, who found that SANDE consistently scored symptoms higher than OSDI in various groups of patients with DED. 17 A difference of 14 points would be, in fact, of clinical significance according to Miller et al 12 However, when algebraic-vectorial normalization was applied to the scores obtained with both questionnaires, we found a difference of less than 2 units. While the magnitude of this difference remained constant in the two different measurements (baseline and follow-up) the signs alternated between both measurements, supporting the idea that the difference is negligible.…”
Section: Discussionmentioning
confidence: 62%
“…[42][43][44][45][46] Menstrual-phase related symptoms were shown also in contact lens wearers, 47 although other authors disagree. 48 Other parameters do not appear to be affected during the cycle, such as tear osmolarity, 49 tear ferning grade, 50 evaporation rate and tear turnover rate. 48 Taken as a whole, these data confirm that the menstrual cycle may change the ocular surface component over the month, which represents per se a bias in the comparison between females and males.…”
Section: The ''His and Hers'' Ocular Surfacementioning
confidence: 95%
“…23 It should be also mentioned that the OSDI questionnaire has been found to be useful as a diagnostic test for differentiating between dry eye and non-dry eye subjects. 24,25 For this study, the Spanish validated version of the OSDI questionnaire was used 26 and a score of less than 22 considered. This limit has been found to be useful for discriminating those patients with minimal or no symptoms potentially associated to dry eye.…”
Section: Methods Patientsmentioning
confidence: 99%